PENGARUH PENERAPAN IKLIM ORGANISASI DAN ETIKA ORGANISASI TERHADAP PERILAKU PEMBELAJARAN ORGANISASI SERTA DAMPAKNYA PADA KINERJA KARYAWAN PATRA SEMARANG CONVENTION HOTEL DI SEMARANG - Rustiana, Ade (PRESTASI, 2010)
This research aimed at testing the presence of influence of organizational climate and ethic implementation on the organizational learning behavior of employees of Patra Semarang Convention Hotel and at testing the presence of influence of organizational climate and ethic implementation on employeesâ performance, both directly and indirectly through organizational learning behavior. The sample consisted of 157 employees of Patra Semarang Convention Hotel. The method used in this research was survey with questionnaire. The hypotheses were tested using multiple regression and path analysis.The research result found that there was an influence of organizational climate and ethic implementation on employeesâ performance, both directly and indirectly through organizational learning behavior of employees of Patra Semarang Convention Hotel. It showed that employeesâ performance improved due to the presence of employeesâ learning behavior and having implemented the organizational climate and ethic well. Keywords : organizational climate, organizational ethic, learning behavior, employeesâ performanceÂ